2005
DOI: 10.1002/bip.20281
|View full text |Cite
|
Sign up to set email alerts
|

The effects of poly(ethylene glycol) on the solution structure of human serum albumin

Abstract: Protein physical and chemical properties can be altered by polymer interaction. The presence of several high affinity binding sites on human serum albumin (HSA) makes it a possible target for many organic and polymer molecules. This study was designed to examine the interaction of HSA with poly(ethylene glycol) (PEG) in aqueous solution at physiological conditions. Fourier transform infrared, ultraviolet-visible, and CD spectroscopic methods were used to determine the polymer binding mode, the binding constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
5
28
0
Order By: Relevance
“…The increase in intensity of amide І and amide ІІ bands are due to PEG binding to protein C]O, CeN and NeH groups. In agreement with previous studies on the interaction of PEG and human serum albumin (HSA) in solution (Ragi, Sedaghat-Herati, Ouameur, & Tajmir-Riahi, 2005;Wu, Wang, Lin, & Chen, 2013), our study found no alteration to BSA secondary structure.…”
Section: Ftir Analysissupporting
confidence: 94%
“…The increase in intensity of amide І and amide ІІ bands are due to PEG binding to protein C]O, CeN and NeH groups. In agreement with previous studies on the interaction of PEG and human serum albumin (HSA) in solution (Ragi, Sedaghat-Herati, Ouameur, & Tajmir-Riahi, 2005;Wu, Wang, Lin, & Chen, 2013), our study found no alteration to BSA secondary structure.…”
Section: Ftir Analysissupporting
confidence: 94%
“…In another study [12] it was shown that PEG at low concentrations had no effect on the secondary structure while on increasing the concentration a considerable decrease in structure was observed. It has been found that PEGs tend to have different effects on different proteins depending upon their chemical nature.…”
Section: Mg-like State Of Con-a Under the Influence Of Different Molementioning
confidence: 93%
“…Protein physical and chemical properties can also be altered by polymer interaction [12]. The PEG polymers are a series of nonionic polyhydroxyl compounds that are miscible with water and display colligative properties in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have reported on inhibition of fibrillation as well as destabilization of preformed fibrils using polyphenols [13,14]. Polyethylene glycols (PEGs) are nontoxic, biocompatible, water-soluble, hydrophilic non-ionic polymers that can interact with proteins through hydrogenbonding or hydrophobic interactions [15][16][17]. They have potential protective effects on various types of protein denaturation [18].…”
Section: Introductionmentioning
confidence: 99%